Empowerment of Agriculture Communities Through Financing Programs - Rohayati Suci Indrianingsih; Perdi Setiawan (Research Collaboration Community (RCC), 2020)
The welfare of actors in the agricultural sector must be guaranteed considering their role in the economy. But often the welfare of farmers is still classified as less prosperous, so empowerment is needed. This study aims to find out about the implementation of agricultural financing and its role in empowering agricultural communities. The method is Systematic Literature Review (SLR). The data used is sourced from journal articles searched through Google Scholar. The results of the study show that there are many types of agricultural financing applied in Indonesia. These various financing programs have a positive role in empowering agricultural communities. Through empowerment programs, the community becomes more empowered and can improve their welfare. Recommendations that can be given are that it is necessary to pay attention to various sources of financing that are in favor of farmers so that they can become a bridge to empowering agricultural communities.